2017
DOI: 10.1093/cvr/cvx180
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TUG1 sponges miR-204-5p to promote osteoblast differentiation through upregulating Runx2 in aortic valve calcification

Abstract: All together, the evidence generated by our study elucidates the role of lncRNA TUG1 as a miRNA sponge in CAVD, and sheds new light on lncRNA-directed diagnostics and therapeutics in CAVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
140
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(143 citation statements)
references
References 49 publications
3
140
0
Order By: Relevance
“…Accumulated studies have demonstrated a significant role for long noncoding RNAs (lncRNAs) in regulating gene expression, including a significant influence on biological activities in the skeletal system, such as in osteoporosis and osteoarthritis . For example, lncRNA TUG1 promoted the differentiation of osteoblast by sponging miR‐204‐5p, which led to the up‐regulation of Runx2 . LncRNA MEG3 restrained the osteogenic differentiation of BMSCs by targeting miR‐133a‐3p .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated studies have demonstrated a significant role for long noncoding RNAs (lncRNAs) in regulating gene expression, including a significant influence on biological activities in the skeletal system, such as in osteoporosis and osteoarthritis . For example, lncRNA TUG1 promoted the differentiation of osteoblast by sponging miR‐204‐5p, which led to the up‐regulation of Runx2 . LncRNA MEG3 restrained the osteogenic differentiation of BMSCs by targeting miR‐133a‐3p .…”
Section: Introductionmentioning
confidence: 99%
“…7 For example, lncRNA TUG1 promoted the differentiation of osteoblast by sponging miR-204-5p, which led to the up-regulation of Runx2. 8 LncRNA MEG3 restrained the osteogenic differentiation of BMSCs by targeting miR-133a-3p. 9 Some studies also revealed that lncRNAs acted as epigenetic regulators in the osteo-adipogenic lineage commitment because of the reciprocal relationship between osteogenic and adipogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…TUG1 has been reported to play critical roles in the progression of many human diseases, such as cancer, aortic valve calcification and pre-eclampsia. [8][9][10] Indeed, TUG1 can regulate gene expression via diverse mechanisms during various biological processes, including inflammatory response. Overexpression of TUG1 has been shown to protect the mouse liver against cold-induced injury by inhibiting apoptosis and inflammation, 11 whereas TUG1 knockdown inhibits hyperlipidaemia, decreases inflammatory response and alleviates atherosclerotic lesions.…”
mentioning
confidence: 99%
“…Bioinformatics algorithm found that miR-204-5p was a target gene of LOC285758. miR-204 was previously reported to be involved in a series of physiological and pathological processes, such as diabetic retinopathy, aortic valve disease and ulcerative disease [25][26][27]. Some recent studies revealed that miR-204-5p also exerts antitumor effects on various cancers (e.g., breast cancer, melanoma and liver cancer) through inhibiting invasion and metastasis of cancer cells [25,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%